Management Perceptions of Share Repurchases in Emerging Markets: The Case for Malaysia - Lee Siew-Peng; Mansor Isa (Asian Academy of Management Journal of Accounting and Finance, 2015)
The purpose of this paper is to study the perceptions of Malaysian chief finance officers (CFO) concerning their reasons for repurchasing shares. We sent a survey questionnaire to the chief finance officers of all the companies listed on the Malaysian Stock Exchange that made repurchase announcements over the period 1 September 1997 until 31 December 2011. The results indicate that the main reason for Malaysian companies to engage in share repurchases is to protect their share prices from market undervaluation. This reason supports the signalling hypothesis, which is found in most of the empirical studies on market reaction to share repurchase announcements. Other repurchase motives, such as to increase EPS, to adjust capital structure, and to use as a substitute for cash dividend received less support from our respondents. These findings are useful, especially to investors for understanding the intention of companies to repurchase shares.